Analysis of Groundwater Softening Methods - ogli, Rakhmatilllayev Yosunbek Ne’matilla (Journal of Higher Education and Academic Advancement, 2024)
In order to increase the demand for water for the population and industrial enterprises and to solve this problem, in order to efficiently use groundwater, protect them from any pollution and compare methods used to date to soften hard water. To soften the groundwater, we offer a method of softening hard water using modern devices and filters created not only by our state, but also by foreign scientists.